Statin therapy intensity and physical activity after acute coronary syndrome. (3rd October 2022) - Boudon, A; Locatelli, I; Gencer, B; Carballo, D; Klingenberg, R; Raeber, L; Windecker, S; Rodondi, N; Luescher, T F; Matter, C M; Mach, F M; Muller, O; et al.
Abstract: Introduction/Purpose: High-intensity statin after acute coronary syndrome (ACS) may cause reduced physical activity because of statin-associated muscle symptoms. We aimed to assess the association between statin intensity and physical activity one year after ACS. Methods: We studied patients from the Special Program University Medicine-Acute Coronary Syndromes (SPUM-ACS) study, a large multicenter prospective Swiss cohort. In a cross-sectional assessment one year after the index ACS, we identified high-intensity, low/moderate intensity, and no statin users. Physical activity was assessed with the International Physical Activity Questionnaire (IPAQ). Using a multivariable adjusted negative binomial hurdle model, metabolic equivalent-minutes per week (MET-min/week) were first stratified into sedentary and physically active categories, and then analyzed continuously among physically active patients. Models were adjusted for age, sex, education, body mass index, depression, type of ACS, pre-existing chronic disease, premature coronary heart disease, LDL-cholesterol, anti-hypertensive treatment, cardiac rehabilitation, and follow-up medical visits after hospital discharge. Results: Among the 2274 patients included in the SPUM-ACS cohort, 1222 (53.7%) were on high intensity statin, 890 (39.1%) on low/moderate intensity statin, and 162 (7.1%) were not on statin. Compared to no statin users, low/moderate intensity statin users were more likely to be physically active than sedentary, with a fully adjusted odds ratio (OR) of 2.78, 95% confidence interval (CI) 1.11–6.93. A similar association was found when comparing non-users with high-intensity statin users, with a fully adjusted OR of 4.18, 95% CI 1.65–10.60. Among physically active patients, physical activity level median scores were 2792.5 MET-min/week in no statin category, 2712.0 and 2839.5 in moderate/low statin category and high statin category respectively (p=0.307), showing no statistically significant difference with median ratios of 1.02, 95% CI 0.84–1.22 and 1.06, 95% CI of 0.88–1.27 for low/moderate intensity and high-intensity statin use, respectively. Conclusion: One year after an ACS, neither low/moderate nor high-intensity statin was associated with reduced physical activity compared to no statin use. These findings go against the belief that statin therapy may lead to reduced physical activity among ACS patients because of associated muscular symptoms. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Center for primary care and public health (Unisanté)